The Research Progress of Single-Molecule Sequencing and Its Significance in Nucleic Acid Metrology - Yajun Wang; Jingjing Liu; Zhendong Wang; Mei Zhang; Yongzhuo Zhang (Biosensors)
Single-molecule sequencing technology, a novel method for gene sequencing, utilizes nano-sized materials to detect electrical and fluorescent signals. Compared to traditional Sanger sequencing and next-generation sequencing technologies, it offers significant advantages, including ultra-long read lengths, rapid sequencing, and the absence of amplification steps, making it widely applicable across various fields. By examining the development and components of single-molecule sequencing technology, it becomes clear that its unique characteristics provide new opportunities for advancing metrological traceability. Notably, its direct detection capabilities offer a novel approach to nucleic acid metrology. This paper provides a detailed overview of library construction, signal generation and detection, and data analysis methods in single-molecule sequencing and discusses its implications for nucleic acid metrology.